Evaluation of High Capacity Helical Piles in Silty Clay (Journal of Civil Engineering Researchers, 2026)
A new foundation system employing in situ grouting of helical screw piles has recently been developed. The paper discusses design considerations, installation procedures and results of full scale field load tests. This study assessed axial static loading tests on single, double and triple helix helical piles under grouted and un-grouted conditions. The field study was conducted to investigate the behavior of helical piles in silty clay soil. Also, the ultimate load capacity (Qu) for each pile test was predicted using six different interpretation methods. Also, the effect of post-grouting on the strength of these piles was assessed and the results of the piles load tests were interpreted using 6 methods presented in literature to predict the ultimate load capacity (Qu) for each pile. Results showed that the grouted helical piles are excellent foundation systems for the resistance of uplift, as well as, compressive loads and  resistance against corrosion and less harmful to the environment than other types of piles especially in urban areas.
Keywords: Capacity; Helical piles; Post Grouting; Silty Clay; Soil Mechanics